Digital transformation readiness on coffee farmers supply chain - Nazila Rahmah Hasan; Amelia Natasya Abdul Wahab; Hazura Mohamed; Mohd Syazwan Baharuddin (Penerbit Universiti Kebangsaan Malaysia, 2025)
The digitalization of agriculture has transformed supply chain management, enhancing efficiency and competitiveness. Recognizing this shift, the Indonesian government has introduced various digital empowerment programs to support farmers in adapting to new business environments. One such initiative in Paya Tumpi Baru village (PTB) led to the development of Pasar Desa Digital (PDD), an e-commerce platform to improve market access for coffee farmers. Despite its potential benefits, many farmers struggle to utilize PDD effectively due to limited digital literacy and understanding, raising concerns about their readiness for digital transformation. This study aims to identify key human resource factors influencing digital transformation readiness in the agricultural sector. A quantitative approach was employed using a survey method to assess 182 coffee farmers in PTB, providing insight into their readiness for digital transformation. The data were subsequently analyzed using descriptive analysis methods by calculating the Respondents' Access Level (RAL) of the farmers. A literature review identified six key factors, which are personnel motivation, ability to learn, commitment, optimism, skill, and knowledge, and these were validated by experts. A structured questionnaire was distributed to measure farmers' level of readiness based on these factors. Results show that 75% of experts agree on the significance of these factors in digital transformation readiness. The assessment of PTB coffee farmers indicates readiness in personnel motivation, commitment, and optimism, moderate readiness in skill; but a lack of preparedness in learning ability and knowledge. Based on these findings, this study provides recommendations to strengthen digital readiness in the agricultural sector, such as training programs and digital literacy workshops, which are essential to bridge the gap and enhance overall readiness, particularly in human resource development.